Increasing frequency of iatrogenic fistula- a new challenge - Tasnim, Nasira; Bangash, Kauser; Amin, Oreekha; Batool, Afshan; Javed, Nosheela (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To determine the frequency of iatrogenic urogenital fistula in patients admitted for the repair of fistula in MCH, Pakistan Institute of Medical Sciences, Islamabad. Methods: The retrospective analysis was conducted at MCH PIMS, Islamabad. It comprised data related to patients having undergone urogenital fistula repair. Statistical analysis of the record was done using SPSS 21 software. Results: Total 98 patients were analyzed. Themean age of patients was 31.6. Out of these, 67.3% of fistulas were attributed to iatrogenic causes while 32.7% were due to obstructed labour. The iatrogenic fistula included post instrumental delivery (5.1%), caesarian section (8.2%), caesarean hysterectomy (17.3%), hysterectomy (36.7%). The fistula caused by obstructed labour included post caesarian section (23.5%) and post normal delivery (9.2%). Conclusions: Our study data showed rising trend of iatrogenic fistula as compared to obstructed labour. This emphasizes the need of optimization of the surgical approach training along with improved obstetric skills, especially in the periphery. Keywords: iatrogenic fistula, obstetric skills, delivery